Solvatochromic and application in dye-sensitized solar cells of sandwich-like Cd(ii) complexes: supramolecular architectures based on N1, N3-bis[(6-methoxypyridin-2-yl)methylene]benzene-1, 3-diamine1. Issue 11 (21st March 2015) - Wang, Xin-Ming; Wang, Ping; Fan, Rui-Qing; Xu, Meng-Ying; Qiang, Liang-Sheng; Wei, Li-Guo; Yang, Yu-Lin; Wang, Yu-Lei
<x xml:space="preserve">Abstract</x> Co-sensitizers 1 and 2 exhibited solvatochromism and fluorescence quenching behavior to CH3OH.